Near-nerve needle sensory and medial plantar nerve conduction studies in patients with small-fiber sensory neuropathy - ULUÇ, KAYIHAN (WILEY, 2008)
The aim of this prospective study was to show and compare the rate of large-fiber involvement with near-nerve needle sensory (NNNS) nerve conduction study (NCS) and with medial plantar NCS recorded with surface electrodes in a group of patients who had clinically pure small-fiber sensory neuropathy (SFSN) with reduced intra-epidermal nerve fiber density in skin biopsy and with normal routine NCS. The study included 19 patients with clinically pure SFSN with normal routine NCS results and 17 healthy volunteers. Routine NCS, skin biopsy, medial plantar NCS and NNNS NCS were performed. NNNS NCS data were evaluated both by using univariate analysis methods and by using a multivariate analysis method, principal components analysis (PCA). Eight patients (42%) had abnormal results for medial plantar NCS with surface electrodes. Seven patients (37%) had abnormal results for NNNS NCS with PCA, whilst only four patients with univariate analysis. We found a significant correlation between intra-epidermal nerve fiber densities, medial plantar NCS and PCA results of NNNS NCS. This study showed that large-nerve fibers are also involved in some patients with pure SFSN and medial plantar NCS can accurately diagnose neuropathy without a need for NNNS NCS in patients with normal routine NCS.
Keywords: intra-epidermal nerve fiber analysis; large-fiber involvement; medial plantar nerve; near-nerve needle technique; small-fiber sensory neuropathy; SKIN BIOPSY; DENSITY; FOOT; POLYNEUROPATHY; UTILITY